(3GdSajfI GdLGeYI dCfhGY GdYdhes - (3GdMSf Hf cQGeI GdLTej GdHjgbj, CHh SYjOs
(3ChdgG (B:s
(3CHhGH ai GdYde hGdYdeGA HGH ai aVd GdYGde hGdYde (B: (3bGd Gddg JYGdi (B" (3bd gd jSJhi GdPjf jYdehf hGdPjf dGjYdehf(B" s
(3BNQgG (B:s
(3BNQg eHJhQ , hBNQ GdehLhO efg CKfGA HGH GdNJe bhdg (B: (3Yf Ybjd bGd (B: (3cGf QShd Gddg Udi Gddg Ydjg jNJe ai jejfg s
(3LRA efgGs
(3HChdgG agQS ddehVhYGJ eHJhQs
(3djS GdcJGH gh TaGA GdMdhe hVjGA GdYdhe ceG cJH HNW eZGjQ ai Chd GdcJGHs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdeYGQa GdYGeIs